Prinzmetal's angina:reflex cardiovascular response during episode of pain. - Perez-Gomez, F (1979)
Previous angiographic studies have shown that coronary spasm occurs in association with the variant angina described by Prinzmetal, confirming his original hypothesis. In this work we recorded the heart rate changes and the incidence of arrhythmias during variant angina. The patients were divided into two groups: anterior, with electrocardiographic signs of anterior ischaemia, and inferior, with changes in the inferior leads. There was a significant increase of heart rate during pain in anterior myocardial ischaemia and a significant decrease when the ischaemia was inferior. The incidence of ectopic arrhythmias during pain was significantly greater in patients with anterior ischaemia, but there was a high incidence of atrioventricular block in patients with inferior ischaemia. We suggest that these findings can be explained by different responses of the automatic nervous system to anterior and inferior acute myocardial ischaemia.